The Effect of Aging in Inhibitory Control of Major Depressive Disorder Revealed by Event-Related Potentials - Zhang, Bing-Wei; Xu, Jing; Chang, Yi (Frontiers in Human Neuroscience, 2016)
Elderly depressed patients manifest pronounced executive dysfunction compared with younger subjects with depressive disorder. Aging-related brain changes may result in executive dysfunction in geriatric depression. We investigated the neural correlates of inhibitory control processing in depressed subjects at different ages using event-related potentials (ERPs). A equiprobable visual Go/Nogo task was used in 19 young (27.4 ± 5.0 years) and 18 elderly (70.8 ± 6.9 years) depressed subjects and their age-matched healthy controls (20 young subjects, 26.2 ± 3.7 years, and 18 elderly subjects, 68.1 ± 4.8 years). The responses were based on two types of equilateral triangular figures of upright (Go) and inverted triangle (Nogo). The elderly subjects exhibited later N2 and P3 latencies, and larger Go-N2 and P3 amplitudes, compared with the younger subjects. Further, the elderly controls displayed smaller P3 in the central and parietal regions, and yielded larger Nogo-P3 amplitude in the frontal region compared with younger controls. While the young depressed patients yielded smaller P3 amplitude than the controls across frontal, central and parietal regions, elderly depressed patients yielded smaller P3 than the elderly controls only in the frontal region. Our results suggest that the inhibitory control subprocesses are differentially affected by depression and aging. The stimulus response speed and the effort intensity of inhibition control are specifically impaired in the elderly depressed patients. And the diminished amplitudes of frontal P3 in the elderly depression imply a frontal dysfunction mechanism.